2022
DOI: 10.1177/00469580221100148
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Predictors of Knowledge, Attitude, and Practice Regarding the Health Hazards Associated With Barber’s Profession in Fiji

Abstract: Introduction: This study aimed to determine the level and predictors of Knowledge, Attitude and Practice (KAP) among barbers regarding health hazards associated with their profession in Fiji. Methods: A quantitative study was used to assess the levels and predictors of KAP using a structured questionnaire among 117 barbers who were chosen between June and November 2020 in Suva, Fiji. All those barbershops that operated at least for 6 months, were licensed, and 18 years and above were included. A self-administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We used Bloom's cut-off point to categorise the level of knowledge, attitude, and practice of healthcare professionals and caregivers regarding NPIs for managing BPSD as follows: scores of ≥ 80% was marked as good knowledge, positive attitude, and good practice, score of 60-79% was categorised as moderate knowledge, neutral attitude, and fair practice, and scores of less than 60% was considered as low knowledge, negative attitude, and poor practice, respectively [35][36][37][38][39][40][41]. Familiarity rating of respondents to each of the 25 NPIs for the four knowledge questions ranged from 'not at all familiar' to 'extremely familiar'.…”
Section: Discussionmentioning
confidence: 99%
“…We used Bloom's cut-off point to categorise the level of knowledge, attitude, and practice of healthcare professionals and caregivers regarding NPIs for managing BPSD as follows: scores of ≥ 80% was marked as good knowledge, positive attitude, and good practice, score of 60-79% was categorised as moderate knowledge, neutral attitude, and fair practice, and scores of less than 60% was considered as low knowledge, negative attitude, and poor practice, respectively [35][36][37][38][39][40][41]. Familiarity rating of respondents to each of the 25 NPIs for the four knowledge questions ranged from 'not at all familiar' to 'extremely familiar'.…”
Section: Discussionmentioning
confidence: 99%
“…The overall participants’ knowledge was categorised using a modified version of Bloom’s cut-off points. Scores between 80% and 100% were categorised as “Good”, scores between 50% and 79% were categorised as “Moderate” and those below 50% were categorised as “Poor” [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies found similar results. 3,5,11,12,14 Some studies found, barbers had Adequate knowledge regarding BBVI, 1,6,15 it might be due to difference in level of education.…”
Section: Knowledge Of Barbers Regarding Bbvimentioning
confidence: 99%
“…Absence or gaps in knowledge, attitude, and practices (KAP) regarding these diseases are associated with occupation of barbers by improper decontamination and prevention methods might provide a medium for spread of these communicable diseases. 1 Blood borne viral infections (BBVI) is a serious public health issue. 2 Common causative agents of BBVI are Hepatitis B virus (HBV), Hepatitis C virus (HCV), and Human Immunodeficiency Virus (HIV).…”
Section: Introductionmentioning
confidence: 99%